Proliferation in human gastrointestinal epithelium using bromodeoxyuridine in vivo: data for different sites, proximity to a tumour, and polyposis coli. Issue 4 (April 1992) - Potten, C S; Kellett, M; Rew, D A; Roberts, S A
Abstract : The distribution of DNA synthesising cells in the crypts of the epithelium in human small and large bowel after injection of bromodeoxyuridine into patients has been studied in relation to the position of the cells in the crypt using immunohistochemistry. Different sites of normal epithelium have been studied. The ileum has a shorter crypt and a very significantly smaller total cell population size. However, it has similar peak labelling index (LI) values to the colon, while the rectum has a lower peak LI value. The mean position of the label occurs at the 17th cell position in the ileum and at about the 22nd position in both the colon and rectum. The overall mean LI is significantly higher in the ileum at 17.8%, intermediate in the colon at 10.3%, and lowest in the rectum at 8.5%. There is thus an inverse relation between the likelihood of developing a tumour and the rate of cell proliferation as measured by the LI. Assuming a value of 8.6 hours for the duration of S, the data suggest that the cell cycle time in the mid crypt region is about 30 hours for the ileum and colon and about 37 hours for the rectum. Samples taken adjacent (within 1 cm) to a tumour show a general dampening of proliferative activity at all cell positions compared with samples taken more than 5 cm from a tumour. This is illustrated by the average LI, which is about 5.4% in the colon adjacent to a tumour compared with 10% distant; comparable values for the rectum are 4.6% and 8.5%. Samples taken from two patients with polyposis coli show distributions with a significant difference in skewness compared with normal colon and a general shifting of the distribution to the right, that is to higher cell positions. There is a significant increase in the mean cell position and the position of the peak LI in the polyposis coli samples.